A Case of Late Supratentorial Seedling of Medulloblastoma - Pandit, Rajeev Kumar; Lama, Manik Kumar; Gurung, Pritam; Rajbhandari, Pravesh (Nepal Journal of Neuroscience, 2025)
Medulloblastoma is a common infratentorial malignant tumour in children. This case was previously diagnosed with infratentorial medulloblastoma and was operated and completed chemo-radiotherapy and was regular follow up. On follow up scan he had tumour in sellar and suprasellar space and he underwent surgery. Histopathological examination showed medulloblastoma.